Nano onion carbon composite lithium iron phosphate positive electrode material as well as preparation method and application thereof
Through the composite of nano-onion carbon and lithium iron phosphate, the poor conductivity of lithium iron phosphate materials is solved, and the particle size reduction, electrochemical polarization reduction and discharge specific capacity are achieved.
Patent Information
- Application Number
- CN202510211909.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-11
AI Technical Summary
The poor conductivity of existing lithium iron phosphate materials leads to a long diffusion distance of lithium ions, poor electron transport, and it is difficult for the carbon cladding to further improve its performance after the material is prepared.
Nano onion carbon is combined with lithium iron phosphate, and nano onion carbon is prepared by roasting nanodiamond powder under a nitrogen atmosphere, and mixed with lithium, iron and phosphorus sources for ball milling and calcining to prepare nano onion carbon composite lithium iron phosphate positive electrode material.
The addition of nano-onion carbon reduces the particle size of lithium iron phosphate, reduces electrochemical polarization, shortens the potential difference of the redox reaction, improves the redox peak current and reaction reversibility, and increases the discharge specific capacity of lithium iron phosphate by more than 38.3%.
Smart Images

Figure CN119812284A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a nano-onion carbon composite lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Since lithium iron phosphate materials have poor intrinsic conductivity, they need to be modified by surface modification to improve their conductivity. The ion diffusion can be improved by reducing the particle size during material preparation through nano-sizing, thereby shortening the diffusion distance of lithium ions in the particles. Nanoparticles are active in nature and have low tap density. The transmission of electrons requires a carbon coating to reduce the polarization of charges on the surface of lithium iron phosphate. After the material is prepared, efforts can be made to further improve the carbon coating of lithium iron phosphate particles, which is expected to improve the tap density and electrochemical performance.
[0003] Carbon nanomaterials have become a research hotspot in environmental protection materials in recent years due to their excellent optical, electrical and mechanical properties. They have shown broad application prospects in the friction research of micro-nano thin film coatings, bioimaging, sensors, photocatalysis, light-emitting diodes, targeted drug transport, composite structural materials, etc. In addition, carbon nanomaterials have high carrier transport properties, which also makes carbon nanomaterials have high application potential in photovoltaic devices. According to literature reports, carbon materials such as CDS, CNTS, CNR, and graphene can be used as dopants to effectively improve the performance of photovoltaic devices, and they can also be used as interface materials to improve charge transport.
[0004] However, most of the carbon materials currently used in organic polymer solar cells have an amorphous structure, while carbon materials with a crystalline skeleton structure often have better electrical properties. In carbon materials with a crystalline skeleton structure, the vibration of atomic bonds in the graphite framework, changes in interlayer spacing, and disordered carbon ring structures will produce porous structures and form some interesting microstructures, thus leading to some peculiar electrochemical characteristics.
[0005] Therefore, how to apply carbon materials with crystalline skeleton structure to lithium iron phosphate materials has received more and more attention. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the embodiment of the present invention provides a method for preparing a nano-onion carbon composite lithium iron phosphate positive electrode material, wherein the nano-onion carbon added to the prepared positive electrode material can hinder the growth and agglomeration of lithium iron phosphate, thereby reducing the size of the synthesized lithium iron phosphate particles; in addition, the addition of nano-onion carbon can reduce the electrochemical polarization of the positive electrode material, shorten the potential difference of the redox reaction, and make the electrochemical reaction easier to proceed.
[0007] The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to the embodiment of the present invention comprises the following steps:
[0008] (1) In a nitrogen atmosphere, the nano-diamond powder is calcined at 1500-1700° C. for 50-70 min and then annealed to obtain nano-onion carbon;
[0009] (2) mixing a lithium source, an iron source, a phosphorus source and the nano-onion carbon obtained in step (1), adding anhydrous ethanol for ball milling, and then drying to obtain a precursor;
[0010] (3) The precursor obtained in step (2) is calcined under vacuum to obtain a nano-onion carbon composite lithium iron phosphate positive electrode material.
[0011] The advantages and technical effects brought by the preparation method of the nano-onion carbon composite lithium iron phosphate positive electrode material of the embodiment of the present invention are as follows: 1. In the method of the embodiment of the present invention, the nano-onion carbon added to the prepared positive electrode material can hinder the growth and agglomeration of lithium iron phosphate, so that the size of the synthesized lithium iron phosphate particles is reduced; 2. In the method of the embodiment of the present invention, the addition of nano-onion carbon can reduce the electrochemical polarization of the positive electrode material, shorten the potential difference of the redox reaction, and make the electrochemical reaction easier to carry out; 3. In the method of the embodiment of the present invention, the coating layer formed by the nano-onion carbon increases the redox peak current, shortens the conduction distance of electrons, makes the redox reaction of the electrode more stable, and has better redox reaction reversibility; 4. In the method of the embodiment of the present invention, the nano-onion carbon can play a role similar to that of a conductive agent, and increase the discharge specific capacity of lithium iron phosphate by more than 38.3%.
[0012] In some embodiments, in step (1), the method for preparing the nano-diamond powder comprises:
[0013] (a) detonating a mixture of TNT and RDX in the presence of water, nitrogen and carbon dioxide in a closed container, and collecting detonation ash from the inner wall of the container;
[0014] (b) eluting the detonation soot obtained in step (a) with a mixed acid solution of sulfuric acid and nitric acid, and conveying it to an acidification device for acidification treatment, and then filtering it and conveying the solid material to an ultrasonic dispersion device for ultrasonic dispersion treatment;
[0015] (c) drying the dispersion obtained by ultrasonic dispersion treatment in step (b) to obtain nano-diamond powder.
[0016] In some embodiments, in step (a), the mass ratio of TNT to RDX is 1:1 to 3;
[0017] And / or, in the step (b), the mass ratio of sulfuric acid to nitric acid in the mixed acid solution is 2 to 5:1; the pH of the acidification treatment is 0.1 to 2; the temperature of the acidification treatment is 70 to 80° C.; and the medium of the ultrasonic dispersion treatment is anhydrous ethanol;
[0018] And / or, in the step (c), the concentration of the dispersion is 0.5 to 5 mg / mL; the temperature of the drying treatment is 60 to 80° C., and the time of the drying treatment is 2 to 5 hours.
[0019] In some embodiments, in step (1), the temperature is increased to 1500-1700° C. at a heating rate of 8-12° C. / min.
[0020] In some embodiments, in step (2), the lithium source includes lithium dihydrogen phosphate;
[0021] And / or, the iron source includes at least one of ferrous oxide, ferrous oxalate or ferric phosphate;
[0022] And / or, the phosphorus source includes at least one of lithium dihydrogen phosphate or iron phosphate.
[0023] In some embodiments, in step (2), the lithium source, iron source and phosphorus source are used in a molar ratio of Li, Fe and P of 0.95:1-2:1-2;
[0024] And / or, the amount of nano-onion carbon added to the precursor is 2-5wt%.
[0025] In some embodiments, in step (2), the ball milling speed is 300 to 500 rpm, and the ball milling time is 10 to 15 hours;
[0026] And / or, the drying treatment temperature is 70-90° C., and the drying treatment time is 8-12 hours.
[0027] In some embodiments, in step (3), the vacuum degree of the calcination process is 10 -2 ~10 -3 Pa, the calcination temperature is 550-700° C., and the calcination time is 0.5-2 h.
[0028] The embodiment of the present invention also provides a nano-onion carbon composite lithium iron phosphate positive electrode material, which is prepared by the above method.
[0029] The present invention also provides the nano-onion carbon composite lithium iron phosphate positive electrode material prepared by the above preparation method or the use of the above nano-onion carbon composite lithium iron phosphate positive electrode material in a positive electrode sheet of a lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the preparation process of nano onion carbon;
[0031] Figure numerals: 1-detonation device, 2-pH meter, 3-acidification device, 4-ultrasonic dispersion device, 5-drying device, 6-high temperature tube furnace. DETAILED DESCRIPTION
[0032] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0033] The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to the embodiment of the present invention comprises the following steps:
[0034] (1) In a nitrogen atmosphere, the nano-diamond powder is calcined at 1500-1700° C. for 50-70 min and then annealed to obtain nano-onion carbon;
[0035] (2) mixing a lithium source, an iron source, a phosphorus source and the nano-onion carbon obtained in step (1), adding anhydrous ethanol for ball milling, and then drying to obtain a precursor;
[0036] (3) The precursor obtained in step (2) is calcined under vacuum to obtain a nano-onion carbon composite lithium iron phosphate positive electrode material.
[0037] The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material in the embodiment of the present invention, the nano-onion carbon added to the prepared positive electrode material can hinder the growth and agglomeration of lithium iron phosphate, so that the size of the synthesized lithium iron phosphate particles is reduced; the method of the embodiment of the present invention, the addition of nano-onion carbon can reduce the electrochemical polarization of the positive electrode material, shorten the potential difference of the redox reaction, and make the electrochemical reaction easier to carry out; the method of the embodiment of the present invention, the coating layer formed by the nano-onion carbon increases the redox peak current, shortens the conduction distance of electrons, makes the redox reaction of the electrode more stable, and has better redox reaction reversibility; the method of the embodiment of the present invention, the nano-onion carbon can play a role similar to that of a conductive agent, and increase the discharge specific capacity of lithium iron phosphate by more than 38.3%.
[0038] like Figure 1 As shown, in some embodiments, preferably, in the step (1), the method for preparing the nano diamond powder comprises:
[0039] (a) detonating a mixture of TNT and RDX in the presence of water, nitrogen and carbon dioxide in a closed container, and collecting detonation ash from the inner wall of the container;
[0040] (b) eluting the detonation soot obtained in step (a) with a mixed acid solution of sulfuric acid and nitric acid, and conveying it to an acidification device for acidification treatment, and then filtering it and conveying the solid material to an ultrasonic dispersion device for ultrasonic dispersion treatment;
[0041] (c) drying the dispersion obtained by ultrasonic dispersion treatment in step (b) to obtain nano-diamond powder.
[0042] In some embodiments, preferably, in the step (a), the mass ratio of TNT (trinitrotoluene) to RDX (cyclotrimethylene trinitramine) is 1:1-3;
[0043] And / or, in the step (b), the mass ratio of sulfuric acid to nitric acid in the mixed acid solution is 2 to 5:1; the pH of the acidification treatment is 0.1 to 2; the temperature of the acidification treatment is 70 to 80° C.; and the medium of the ultrasonic dispersion treatment is anhydrous ethanol;
[0044] And / or, in the step (c), the concentration of the dispersion is 0.5 to 5 mg / mL; the temperature of the drying treatment is 60 to 80° C., and the time of the drying treatment is 2 to 5 hours.
[0045] In some embodiments, preferably, in the step (1), the temperature is increased to 1500-1700° C. at a heating rate of 8-12° C. / min.
[0046] In some embodiments, preferably, in step (2), the lithium source comprises lithium dihydrogen phosphate;
[0047] And / or, the iron source includes at least one of ferrous oxide, ferrous oxalate or ferric phosphate;
[0048] And / or, the phosphorus source includes at least one of lithium dihydrogen phosphate or iron phosphate.
[0049] In some embodiments, preferably, in the step (2), the lithium source, iron source and phosphorus source are used in a molar ratio of Li, Fe and P of 0.95:1-2:1-2;
[0050] And / or, the amount of nano-onion carbon added to the precursor is 2-5wt%.
[0051] In some embodiments, preferably, in the step (2), the ball milling speed is 300 to 500 rpm, and the ball milling time is 10 to 15 hours;
[0052] And / or, the drying treatment temperature is 70-90° C., and the drying treatment time is 8-12 hours.
[0053] In some embodiments, preferably, in step (3), the vacuum degree of the calcination process is 10 -2 ~10 - 3 Pa, the calcination temperature is 550-700° C., and the calcination time is 0.5-2 h.
[0054] In the embodiment of the present invention, the calcination treatment conditions are preferably selected, which can make the synthesized lithium iron phosphate free of impurities, and the nano-onion carbon hinders the growth of lithium iron phosphate grains, so that smaller lithium iron phosphate particles can be obtained.
[0055] The embodiment of the present invention also provides a nano-onion carbon composite lithium iron phosphate positive electrode material, which is prepared by the above method.
[0056] The present invention also provides the nano-onion carbon composite lithium iron phosphate positive electrode material prepared by the above preparation method or the use of the above nano-onion carbon composite lithium iron phosphate positive electrode material in a positive electrode sheet of a lithium ion battery.
[0057] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.
[0058] Example 1
[0059] (1) using graphite as a precursor material, or using explosives themselves as a carbon source, detonating the mixture in a closed container in the presence of water, nitrogen and carbon dioxide, thereby forming nanodiamonds in the high temperature and high pressure detonation wave of the reactor, and collecting the detonation soot from the inner wall of the device;
[0060] (2) The soot on the inner wall of the detonation device is eluted with a mixed acid solution of H2SO4 and HNO3 in a ratio of 3:1, and transported to an acidification device. The pH inside the acidification device is adjusted to 0.5-1 by a pH meter, and the acidification device is heated and maintained at a temperature of 75°C. After acidification, the solid material is filtered and transported to an ultrasonic dispersion device;
[0061] (3) In an ultrasonic dispersion device, the solid material is dispersed in anhydrous ethanol and ultrasonic waves are used to disperse it evenly. During this ultrasonic process, the concentration of the dispersion is controlled at 3 mg / mL; after ultrasonic dispersion, the material is dried at 70° C. for 4 h using a drying device to obtain nanodiamond dry powder;
[0062] (4) placing 1 g of the obtained nano-diamond powder in a reaction boat with a length of 6 cm, placing the reaction boat in a tubular furnace, heating the temperature to 1500° C. at a heating rate of 10° C. / min under a nitrogen atmosphere, maintaining the highest temperature for 60 min, and then performing annealing treatment to obtain black powder nano-onion carbon (OLC);
[0063] (5) Using OLC as a carbon source, the lithium source, iron source and phosphorus source were synthesized according to the molar ratio of Li:Fe:P=0.95:1:1. Weigh 0.2 mol of the mixture, 100 ml of anhydrous ethanol, put it into a ball mill, add 100 g of stainless steel grinding balls of different sizes, use a planetary ball mill, rotate at 400 rpm, and ball mill for 12 hours. Transfer it to a glass beaker, put it in a blast drying oven, and dry it at 80°C for 10 hours to obtain a dry precursor, in which the addition amount of OLC is 3wt%.
[0064] (6) The precursor obtained by ball milling is placed in a ceramic ark and placed in a vacuum hot press furnace for 10 -2 ~10 -3 Pa, they were calcined at 650°C and kept warm for 1h, and then cooled to room temperature to obtain a nano-onion carbon composite lithium iron phosphate positive electrode material.
[0065] Example 2
[0066] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (4), the temperature is raised to 1600° C. to prepare nano-onion carbon.
[0067] Example 3
[0068] The preparation method of this comparative example is the same as that of Example 1, except that in step (4), the temperature is raised to 1700° C. to prepare nano-onion carbon.
[0069] Comparative Example 1
[0070] The preparation method of this comparative example is the same as that of Example 1, except that in step (4), the temperature is raised to 1400° C. to prepare nano-onion carbon.
[0071] Comparative Example 2
[0072] The preparation method of this comparative example is the same as that of Example 1, except that steps (1) to (4) are eliminated, and graphite is used as the carbon source in step (5), and the amount of graphite added is 3 wt%.
[0073] Comparative Example 3
[0074] The preparation method of this comparative example is the same as that of Example 1, except that steps (1) to (4) are eliminated, and in step (5), only lithium iron phosphate positive electrode material is prepared without adding a carbon source.
[0075] Performance Testing
[0076] The positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare positive electrodes for lithium-ion batteries, which were further assembled into lithium-ion batteries. The performance of the prepared lithium-ion batteries was tested, and the results are shown in Table 1.
[0077] Table 1
[0078] Discharge specific capacity (mAh / g) Example 1 125 Example 2 118 Example 3 120 Comparative Example 1 115 Comparative Example 2 110 Comparative Example 3 90.3
[0079] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0080] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing a nano-onion carbon composite lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: (1) In a nitrogen atmosphere, the nano-diamond powder is calcined at 1500-1700° C. for 50-70 min and then annealed to obtain nano-onion carbon; (2) mixing a lithium source, an iron source, a phosphorus source and the nano-onion carbon obtained in step (1), adding anhydrous ethanol for ball milling, and then drying to obtain a precursor; (3) The precursor obtained in step (2) is calcined under vacuum to obtain a nano-onion carbon composite lithium iron phosphate positive electrode material.
2. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the method for preparing the nano diamond powder comprises: (a) detonating a mixture of TNT and RDX in the presence of water, nitrogen and carbon dioxide in a closed container, and collecting detonation ash from the inner wall of the container; (b) eluting the detonation soot obtained in step (a) with a mixed acid solution of sulfuric acid and nitric acid, and conveying it to an acidification device for acidification treatment, and then filtering it and conveying the solid material to an ultrasonic dispersion device for ultrasonic dispersion treatment; (c) drying the dispersion obtained by ultrasonic dispersion treatment in step (b) to obtain nano-diamond powder.
3. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 2, characterized in that: In the step (a), the mass ratio of TNT to RDX is 1:1-3; And / or, in the step (b), the mass ratio of sulfuric acid to nitric acid in the mixed acid solution is 2 to 5:1; the pH of the acidification treatment is 0.1 to 2; the temperature of the acidification treatment is 70 to 80° C.; and the medium of the ultrasonic dispersion treatment is anhydrous ethanol; And / or, in the step (c), the concentration of the dispersion is 0.5 to 5 mg / mL; the temperature of the drying treatment is 60 to 80° C., and the time of the drying treatment is 2 to 5 hours.
4. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the temperature is increased to 1500-1700° C. at a heating rate of 8-12° C. / min.
5. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the lithium source includes lithium dihydrogen phosphate; And / or, the iron source includes at least one of ferrous oxide, ferrous oxalate or ferric phosphate; And / or, the phosphorus source includes at least one of lithium dihydrogen phosphate or iron phosphate.
6. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 1 or 5, characterized in that: In the step (2), the lithium source, iron source and phosphorus source are used in a molar ratio of Li, Fe and P of 0.95:1-2:1-2; And / or, the amount of nano-onion carbon added to the precursor is 2-5wt%.
7. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the rotation speed of the ball mill is 300 to 500 rpm, and the ball milling time is 10 to 15 hours; And / or, the drying treatment temperature is 70-90° C., and the drying treatment time is 8-12 hours.
8. The method for preparing the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step (3), the vacuum degree of the calcination process is 10 -2 ~10 -3 Pa, the calcination temperature is 550-700° C., and the calcination time is 0.5-2 h.
9. A nano-onion carbon composite lithium iron phosphate positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the nano-onion carbon composite lithium iron phosphate positive electrode material prepared according to any one of the preparation methods of claims 1 to 8 or the nano-onion carbon composite lithium iron phosphate positive electrode material according to claim 9 in a positive electrode sheet of a lithium-ion battery.